Role of Oxygen Supply in Macrophages in a Model of Simulated Orthodontic Tooth Movement - Agnes Schröder; Leonie Barschkies; Jonathan Jantsch; Peter Proff; Lina Gölz; James Deschner; Christian Kirschneck (Mediators of Inflammation)
Apart from periodontal ligament fibroblasts, immune cells like macrophages also play an important mediating role in orthodontic tooth movement (OTM). Upon orthodontic force application to malpositioned teeth, macrophages in the periodontal ligament get exposed to both mechanical strain and hypoxic conditions (via a compression of blood vessels). In this study, we assessed the relative impact of orthodontically induced mechanical strain and hypoxic conditions on macrophages for the mediation and regulation of OTM. Macrophages were stimulated with physiological orthodontic compressive forces of 2 g/cm2 for 4 h and 24 h on gas-impermeable or gas-permeable cell culture plates under normoxic or hypoxic cell culture conditions. We quantified expression of genes involved in inflammation (Tnf, Il-6, and Cox-2), extracellular remodelling (Mmp-9), and angiogenesis (Vegf) by RT-qPCR. Furthermore, we analysed HIF-1α, prostaglandin-E2, and VEGF protein expression via immunoblotting or ELISA. Mechanical strain and oxygen supply both differentially affected expression of genes and proteins involved in inflammation and angiogenesis. In this context, we found that HIF-1α protein levels were elevated by combined mechanical strain and hypoxic conditions, whereas gas-permeable plates providing sufficient oxygen supply prevented HIF-1α stabilization at the protein level after pressure application on macrophages. Our results thus indicate that macrophages involved in the mediation of OTM are affected by and respond differently to hypoxic conditions and mechanical compressive strain, which occur concomitantly during OTM, than periodontal ligament fibroblasts (PDLF), thus indicating different roles of these cells in the regulation of OTM at the cellular-molecular level. We further observed that contrary to PDLF HIF-1α stabilization in macrophages is rather induced via the decreased oxygen supply associated with OTM than via mechanotransduction by mechanical strain.